La expresión corporal en educación inicial de la Unidad Educativa Isidro Ayora ubicado en el cantón Latacunga provincia de Cotopaxi en el año 2016-2017 - Palomo Semblantes, Paulina del Rocío (2017)
An analysis about the subject development was done in this research: "The corporal expression in initial education at “Isidro Ayora” Elementary school located in Latacunga Canton, Province of Cotopaxi during 2016 - 2017" which the objective was to analyze the corporal expression problems to achieve an optimal integral development at the studio place in which once the problem was detected, proceed to the Theoretical Framework building to base appropriately the theme research particularly is the same body expression defined as the discipline that studies motor behavior with an end expressive, communicative and aesthetic in which the body, movement and feeling are basic instruments, is a new art form that owns the human body, its means of expression privileged and could be said that exclusive, that with its development can be achieved in the boy and girl an optimum integral development, based on got information into books, magazines, and internet; qualitative was the research methodology on a study instruments were applied on motor problem processing of coordination to guide the children, parents and authorities respectively with the analysis, proceeding to analyze statistically the data obtained, which allowed to establish the results this study constitutes an important part for the pedagogical development that will serve to strengthen the methodology that the teachers can use in the initial education to achieve an optimal integral development.